Carved in stone: Experimental criteria for identifying Paleolithic bas-relief production techniques and sculptors’ expertise - Émilie Brochard; Luc Doyon; Lloyd A. Courtenay; Gilles Tosello; Lila Geis; Francesco d’Errico (PLoS ONE, 2026)
Paleolithic bas-relief is a rare yet technically demanding form of parietal art whose production methods and skill requirements remain poorly understood. Investigating their production is essential because carving methods and required skills reveal the degree of technical investment, cognitive planning, and craftsmanship mobilized by prehistoric artists. This study presents the first integrated experimental, qualitative, and quantitative investigation of their manufacture. Using Coniacian limestone blocks, we replicated 19 carving modalities, covering pecking, scraping, polishing, engraving, and sequential combinations, executed by participants ranging from novices to a professional sculptor. Each surface was documented through high-resolution photography, Reflectance Transformation Imaging, and 3D scanning, then analyzed via standardized descriptive criteria, roughness measurements, and elliptical Fourier analysis of engraving profiles. Results show that some techniques, such as pecking and engraving, leave distinctive traces, while scraping and polishing often produce overlapping surface signatures, especially when techniques are superimposed. Quantitative data confirm a continuum of surface textures rather than discrete categories and reveal how the sequence of actions can partially obscure earlier marks. Expertise strongly influences mark regularity, efficiency, and isotropy, with the expert producing more controlled and less complex surfaces. The combined qualitative–quantitative approach proved essential: numerical parameters objectively discriminate patterns, but visual assessment remains critical for interpreting surface reliefs in archaeological contexts. By establishing experimentally validated diagnostic criteria for techniques and skill levels, this work provides a robust reference framework for identifying carving methods on archaeological bas-reliefs . The findings open new perspectives for reconstructing chaînes opératoires , assessing knowledge transmission, and exploring the role of specialization in Upper Paleolithic hunter-gatherer societies.